Proteins involved in distinct phases of cold hardening process in frost resistant winter barley (Hordeum vulgare L.) cv Luxor - Hlaváčková, Iva; Vítámvás, Pavel; Santrůček, Jiří; Kosová, Klára; Zelenková, Sylva; Prášil, Ilja Tom; Ovesná, Jaroslava; Hynek, Radovan; Kodíček, Milan (International journal of molecular sciences, 2013)
Winter barley is an economically important cereal crop grown in higher latitudes and altitudes where low temperatures represent an important environmental constraint limiting crop productivity. In this study changes in proteome of leaves and crowns in a frost tolerant winter barley cv. Luxor in relation to short and long term periods of cold followed by a brief frost treatment were studied in order to disclose proteins responsible for the cold hardening process in distinct plant tissues. The mentioned changes have been monitored using two dimensional difference gel electrophoresis (2D-DIGE) with subsequent peptide-mapping protein identification. Regarding approximately 600-700 distinct protein spots detected on 2D gels, there has been found at least a two-fold change after exposure to low temperatures in about 10% of proteins in leaves and 13% of proteins in crowns. Protein and nitrogen metabolic processes have been influenced by low temperature to a similar extent in both tissues while catabolism, carbohydrate metabolism and proteins involved in stress response have been more affected in crowns than in leaves. The range of changes in protein abundance was generally higher in leaves and chloroplast proteins were frequently affected which suggests a priority to protect photosynthetic apparatus. Overall, our data proved existence of slightly different response strategies to low temperature stress in crowns and leaves, i.e., tissues with different biological role. Moreover, there have been found several proteins with large increase in accumulation, e.g., 33 kDa oxygen evolving protein of photosystem II in leaves and "enhanced disease susceptibility 1" in crowns; these proteins might have potential to indicate an enhanced level of frost tolerance in barley.
Keywords: ječmen (rod); 2D gelová elektroforéza; Acclimatization; studené klima; Seasons; Cold Climate; proteom; listy rostlin; Proteome; Plant Proteins; peptidové mapování; Plant Components, Aerial; Plant Leaves; aklimatizace; roční období; Peptide Mapping; rostlinné proteiny; nadzemní části rostlin; Electrophoresis, Gel, Two-Dimensional; Hordeum